2021
DOI: 10.2147/dddt.s327270
|View full text |Cite
|
Sign up to set email alerts
|

Ventilagolin Suppresses Migration, Invasion and Epithelial-Mesenchymal Transition of Hepatocellular Carcinoma Cells by Downregulating Pim-1

Abstract: Inhibition of tumor metastasis is a useful strategy to improve the efficacy of cancer therapy. Ventilagolin, a natural 1, 4-naphthoquinone derivative extracted from Ventilago leiocarpa Benth, has shown promising antitumor effects in previous studies. However, the effects and underlying mechanisms of Ventilagolin against migration, invasion and epithelial-mesenchymal transition (EMT) of hepatocellular carcinoma (HCC) remain unclear. The present study has examined these effects and determined whether the protoon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In different hematological malignancies such as diffuse large B-cell lymphoma (DLBCL), multiple myeloma, and leukemia, as well as solid tumors including prostate, colon, pancreatic, hepatocellular, and breast tumors, both PIM-1 and PIM-2 kinases are often overexpressed. It was also recently reported that PIM-1 may function as an oncogene in cervical cancer by activating EGFR signaling. In addition, PIM-1 kinase has also been associated with various functional aspects such as immunotherapy, aging, and epigenetics . On the other hand, PIM-3 kinase is predominantly overexpressed in solid tumors derived from the prostate, pancreas, and colon.…”
Section: Structures and Biological Functions Of Pimmentioning
confidence: 99%
“…In different hematological malignancies such as diffuse large B-cell lymphoma (DLBCL), multiple myeloma, and leukemia, as well as solid tumors including prostate, colon, pancreatic, hepatocellular, and breast tumors, both PIM-1 and PIM-2 kinases are often overexpressed. It was also recently reported that PIM-1 may function as an oncogene in cervical cancer by activating EGFR signaling. In addition, PIM-1 kinase has also been associated with various functional aspects such as immunotherapy, aging, and epigenetics . On the other hand, PIM-3 kinase is predominantly overexpressed in solid tumors derived from the prostate, pancreas, and colon.…”
Section: Structures and Biological Functions Of Pimmentioning
confidence: 99%
“…The alkaloid CVB-D suppresses proliferation, migration, invasion, and EMT of HCC cell lines by inhibiting the EGFR-FAK-AKT/ERK1/2-Slug signaling pathway in human HCC [ 99 ]. Both in vivo and in vitro studies demonstrate that the alkaloid ventilagolin downregulates the expression of Pim-1, N -cadherin, and vimentin, upregulates the expression of E-cadherin, and inhibits the migration, invasion, and EMT of HCC cells [ 103 ]. These studies collectively confirm that NPs can exert anti-tumor effects by inhibiting migration and invasion.…”
Section: The Main Action Pathway and Potential Mechanism Of Natural C...mentioning
confidence: 99%